2019
DOI: 10.30971/pje.v36i1.1155
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Stress Coping Strategies and Approaches of School Teachers

Abstract: With increasing demands of the job market, occupational stress isbecoming a matter of great concern for both employers and employeesacross the occupations. Individuals try different coping strategies andapproaches to keep this stress at a manageable level. This studyexamined the stress coping strategies and approaches used by the schoolteachers in respect to their perceived level of stress. A self-developedquestionnaire based on COPE inventory was used to conduct this surveybasedexploratory study. A sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The common coping strategies used by the teachers are either discussing it with trustworthy colleagues, crafting their job a little bit, presenting their demand as a team in front of school management, personally hanging out with friends and family, listening to music, arranging, movie nights, trip to hilly areas in off days and other recreational activates etc. recent coping trends observed among Pakistani teachers are "Turning to religion," "positive reinterpretation" and "planning" to actively solve the problem (Hussain, Zulfqar, & Aziz, 2019). Teachers feel less worried and fear changing perceptions, organizational interventions, and coping.…”
Section: In What Circumstances Do Employees Perceive Eustress?mentioning
confidence: 99%
“…The common coping strategies used by the teachers are either discussing it with trustworthy colleagues, crafting their job a little bit, presenting their demand as a team in front of school management, personally hanging out with friends and family, listening to music, arranging, movie nights, trip to hilly areas in off days and other recreational activates etc. recent coping trends observed among Pakistani teachers are "Turning to religion," "positive reinterpretation" and "planning" to actively solve the problem (Hussain, Zulfqar, & Aziz, 2019). Teachers feel less worried and fear changing perceptions, organizational interventions, and coping.…”
Section: In What Circumstances Do Employees Perceive Eustress?mentioning
confidence: 99%
“…The interview guide and setting may further explain why none of the informants mentioned any of the undesirable strategies for coping with stress that are documented in international studies, such as drug abuse (e.g., Richards, 2012) or religion (e.g., Hussain et al, 2019). Another weakness is the lack of other data sources or the use of other methods that could have provided us with additional information.…”
Section: Research Limitations and Future Researchmentioning
confidence: 99%
“…Whereas a study in china byWu, & Chan, (2012) found that in China, teachers use minimum frequency of humour. A study conducted byHussain, Zulfqar, & Aziz, (2019) entitled "Analyzing Stress Coping Strategies and Approaches" of 400 School Teachers with varied backgrounds working in both private and public schools and revealed that 'planning' to actively solve the problem, 'positive reinterpretation' 'Turning to religion', and, emotion-oriented strategies are mostly used strategies, while avoidance and social-support approaches are used least. Similarly, in India which has a similar Education system to Pakistan, A study on 120 teachers in Rajpur city of Chattisgarh, India, was conducted byShukla,…”
mentioning
confidence: 99%